Sejarah desa: Transformasi Desa Pendung Talang Genting dari perkebunan ke kampung santri (1920-2022) - Budi Darmawan; Nuranisa Fitri (Historiography: Journal of Indonesian History and Education, 2023)
This research aims to describe the development of Pendung Talang Genting from pre-colonial times to the independence era focus on geographical, cultural, economic and religious aspects. The method is historical with four main steps: data collection, data testing, data interpretation, and history writing. The community maintains the cultural heritage and customs of their ancestors, maintains local wisdom and Islamic values in various cultural and religious activities. Its economy depends on rice farming and fishing. This village has existed since before Dutch colonialism in Kerinci, and separated from Kemendapoan Seleman in Dutch colonial era, and experienced economic and political interference from the colonials because of its Coffee comodity. With economic development and the influence of Islam, people increased their understanding of religion, which continued until Indonesian independence. In 2009, the Islamic boarding school in Pendung Talang Genting was reopened to strengthen Islamic education and life. Village regulations were also adopted to regulate the community's religious and cultural activities, including rules relating to the wearing of the hijab, participation in Al-Qur'an recitations, and the prohibition of alcohol and drugs. For decades, Pendung Talang Genting Village has maintained its identity as a "Kampung Santri," emphasizing Islamic values, and caring for local cultural heritage.Penelitian ini bertujuan mendeskripsikan perkembangan Desa Pendung Talang Genting dari masa pra-kolonial hingga era kemerdekaan dengan fokus pada aspek geografis, budaya, ekonomi, dan agama. Metodenya adalah sejarah dengan empat langkah utama: pengumpulan data, pengujian data, interpretasi data, dan penulisan sejarah. Masyarakatnya mempertahankan warisan budaya dan adat istiadat dari leluhur, menjaga kearifan lokal dan nilai-nilai Islam dalam berbagai aktivitas budaya dan keagamaan. Ekonominya bergantung pada pertanian padi dan perikanan desa ini telah ada sejak sebelum penjajahan Belanda di Kerinci, dan memisahkan diri dari Kemendapoan Seleman selama masa kolonial Belanda dan mengalami campur tangan ekonomi dan politik dari kolonial karena pertanian kopi. Dengan perkembangan ekonomi dan pengaruh agama Islam, masyarakat meningkatkan pemahaman agama mereka, yang berlanjut hingga kemerdekaan Indonesia. Pada 2009, pesantren di Desa Pendung Talang Genting dibuka kembali untuk memperkuat pendidikan dan kehidupan Islam. Peraturan Desa juga diadopsi untuk mengatur aktivitas keagamaan dan budaya masyarakat, mencakup aturan berkaitan dengan pemakaian jilbab, partisipasi dalam pengajian Al-Qur'an, serta larangan minuman keras dan narkoba. Selama beberapa dekade, Desa Pendung Talang Genting mempertahankan identitasnya sebagai "Kampung Santri", dengan menekankan nilai-nilai Islam dalam kehidupan dan merawat warisan budaya lokal.